Development of speech rhythm in Kannada speaking children - S R, Savithri; N, Sreedevi; T, Jayakumar; V, Kavya (Journal of All India Institute of Speech and Hearing, 2010)
Rhythm in speech is the systematic organization of speech units in time, such as syllables and vocalic intervals. Language of the world has been organized under stress-timed, syllable – timed and mora-timed, depending on the type of syllables used in a language. The present study is initially output of large scale study which to investigated the development of speech rhythm in typically developing Kannada speaking children by using the pair-wise Variability Index (PVI). Total of 15 boys, were divided in to three age groups (4-5, 8-9 and 11-12 years) with an equal number of participants. A five-minute of narrated speech sample of each child was elicited using cartoons or Panchatantra pictures. All the samples were audio-recorded using Olympus digital voice recorder at a sampling frequency of 16 kHz. Each speech samples were audio listened carefully removed the pauses manually. The Vocalic (V) and Intervocalic (IV) durations were measured in the samples using PRAAT software. The duration difference between successive vocalic and intervocalic segments was calculated and averaged to get the normalized Pair-wise Variability Index (nPVI) and raw Pair-wise Variability Index (rPVI), respectively. The result indicated that segmental timing showed a developmental trend in children and the boys begin to adult-like rhythm at around 11-12 years. Due to the high nPVI and low rPVI values the rhythmic pattern remains unclassified and cannot be placed in any of the rhythmic classes. The findings reveal that the syllabic structure used by children is different (prolonged vowel duration) from the adults.